Knitted wrist warmers - Russel, Monica (Tunbridge Wells, Kent Search Press, 2014)
Knit yourself a pair of stylish Wrist Warmers with this book, which offers twenty stylish designs at an unbeatable price
2
NEW
Keywords: Knitting -- Patterns; Knitting